Synchronization of estrus in bovines - HUSSAIN, P MARGOOB; HONNAPPA, T G (The Indian Journal of Animal Reproduction, 2023)
In the present study, 145 sub-estrus cows and buffaloes were randomly divided into two groups and weretreated with 500μg of Prostaglandin (PGFi-cloprostenol) intra~muscularly either as a single injection or twoinjections at nine· days apart. The percentage ·of induced estrus to single PGF2a injection was 83.33 per cent,· . while for double PGF2a injection the response was 88.60 per cent. The time interval for the onset of estrus to· single and double PGF2a injection regime varied between 73.83 ± 2.85 to 7_5.23 ± 5.32 hours and 72.59 ± 3.67to 74.51 ,± 2.42 hours respectively. The overall conception rate on pregnancy diagnosis was recorped to be 69.09and 75.71 per cent respectively for .single and doubh: PGF2a injections.
Keywords: Synchronization; Estrus response; Conception rate; PGF2alpha; dairy animals